Attack on RSA-type cryptosystems based on singular cubic curves over Z/nZ - Chua, Seng Kiat (2013)
Several RSA-type cryptosystems based on singular cubic curves have been proposed in recent years (cf. Koyama, Lecture notes in Computer Science, vol. 921, Springer, Berlin, 1995, pp. 329–339; Kuwakado, IEICE Trans. Fund. E78-A (1995) 27–33; Koyama, IEICE Trans. Fund. E77-A (1994) 1309–1318). We show that these schemes are equivalent and demonstrate that they are insecure if a linear relation is known between two plaintexts.